Efficacy of acupuncture for Parkinson’s disease with mild cognitive impairment: study protocol for a randomized controlled trial - Wu, Shunan; Leong, Ian I.; Fan, Jingqi; Liu, Xin; Liu, Elaine; Lei, Suying; Xu, Xiaoyan; Liao, Kaihao; Zhuang, Li-Xing (Frontiers in Neurology, 2025)
BackgroundParkinson’s disease with mild cognitive impairment (PD-MCI) is one of the primary non-motor symptoms of Parkinson’s disease (PD). PD-MCI represents an early stage of cognitive impairment in PD and serves as a potential precursor to PDD. To date, research on the treatment of mild cognitive impairment in PD remains limited. Acupuncture, a classical therapeutic modality in Traditional Chinese Medicine, exhibits superior therapeutic outcomes to pharmacotherapy for mild cognitive impairment while avoiding drug-associated adverse effects.ObjectiveThis randomized, single-blind clinical trial aims to evaluate the efficacy and safety of acupuncture for PD-MCI. To improve the credibility of acupuncture research evidence through employing a sham acupuncture device as a control.Methods and analysisThis is a prospective, sham-controlled, subject-blinded and assessor-blinded trial, which conducted at a single center in China. A total of 72 eligible PD-MCI volunteers will be randomized using a simple randomization method in a 1:1 ratio into the acupuncture group and the placebo acupuncture group to receive either acupuncture or placebo acupuncture for 20 sessions over a succession of 5 weeks. The primary outcome measure will be the Montreal Cognitive Assessment Scale (MoCA) score. The secondary outcome measures will be the scores of Mini-Mental State Examination (MMSE), Unified Parkinson’s Disease Rating Scale Motor Examination (UPDRSIII) and the level of neurofilament light polypeptide (NfL) and glial cell-derived neurotrophic factor (GDNF). The evaluation will be assessed before and after treatment.DiscussionThis study represents the first randomized, single-blind clinical trial investigating acupuncture treatment for cognitive dysfunction in Parkinson’s disease. An auxiliary device designed by our team, featuring a flat-head needle and adjustable sleeve, will be used for placebo acupuncture procedure to achieve a single-blind effect. Serum NfL and GDNF levels will be incorporated to elucidate the mechanisms underlying acupuncture’s effects and explore specific biomarkers of PD. The aim of this study is to provide reliable clinical evidence for the treatment of PD-MCI and improve patients’ survival and quality of life.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2400082082.